Endoscopic biliary stenting as the risk factor for cholangitis after endoscopic ultrasound in patients with biliary strictures. Issue 5 (29th September 2020) - Ikezawa, Kenji; Shigekawa, Minoru; Yamai, Takuo; Suda, Takahiro; Kegasawa, Tadashi; Yoshioka, Teppei; Sakamori, Ryotaro; Tatsumi, Tomohide; Takehara, Tetsuo
Abstract: Background and Aim: Endoscopic ultrasound (EUS) and EUS‐guided fine needle aspiration (FNA) are established as efficient and safe diagnostic modalities. However, the risk of cholangitis after EUS/EUS‐FNA (post‐EUS cholangitis) in patients who have biliary strictures has not been fully examined. Methods: We retrospectively reviewed 136 consecutive inpatients with biliary strictures who received EUS/EUS‐FNA at our hospital from April 2012 to September 2017 and evaluated complications that occurred by the next day after EUS/EUS‐FNA. Patients with percutaneous biliary drainage, those in whom it was difficult to reach the duodenum, and those receiving concurrent endoscopic retrograde cholangiopancreatography were excluded. Results: We included 121 patients (147 cases); 90 patients were malignant. Endoscopic biliary stenting (EBS) with plastic stents had already been performed in 86 cases. Post‐EUS cholangitis was observed in 4.1% (6/147). No other EUS‐related complications were observed. The incidence of cholangitis with EBS was significantly higher than that in the cases without EBS (7.0% [6/86] vs 0% [0/61], P  = 0.042). Biliary enzyme elevation was also identified as a risk factor of cholangitis. Conclusion: Endoscopic biliary stenting was identified as a risk factor associated with post‐EUS cholangitis in patients with biliary strictures. Endoscopists should pay attention to post‐EUS cholangitis, especially in cases with EBS and biliary enzyme elevation.